Bond slip detection of steel plate and concrete beams using smart aggregates. (22nd October 2015) - Qin, Feng; Kong, Qingzhao; Li, Mo; Mo, Y L; Song, Gangbing; Fan, Feng
Abstract: The newly emerged steel plate concrete (SC), benefited from a composite effect of steel and concrete materials, has been applied to shield building and internal structures of AP1000 nuclear power plants. The detection of bond-slip between steel plate and concrete is of great importance to provide early warnings of steel plate and concrete debonding and to ensure the safety of SC structures. In this paper, an active sensing approach using smart aggregates (SAs) is developed to detect the initiation and to monitor the development of bond-slip. A SA, designed by sandwiching a fragile piezoceramic patch between protection materials, can be utilized as both actuator and sensor by taking advantage of the piezoelectricity of piezoceramic material. Two SC beams with distinct shear reinforcement ratios were experimentally investigated. Based on the wavelet packet decomposition of the received signals from SAs, the initiation of bond-slip is detected, and the development of bond-slip is quantitatively monitored to better understand the structural performance of SC beams, including the stiffness and capacity. The bond-slip severities of the two SC beams are compared to study the improvement of bond-slip condition rendered by providing more shear reinforcement.